Growth, microstructure and mechanical properties of CoCrFeMnNi high entropy alloy films. (September 2020) - Wang, Ze; Wang, Cheng; Zhao, Yi-Lu; Huang, Tzu-Hsuan; Li, Chia-Lin; Kai, Ji-Jung; Liu, Chain-Tsuan; Hsueh, Chun-Hway
Abstract: CoCrFeMnNi high entropy alloy films (HEAFs) manifest excellent properties as the potential structural materials in the microelectro-mechanical systems (MEMS). In this work, we systematically investigated the growth, microstructure and mechanical properties of CoCrFeMnNi HEAFs with thicknesses varying from 300 to 1400 nm. The film growth study revealed that 300 nm of the amorphous layer, 250 nm of the crystalline layer, and the preferred orientation layer grew sequentially during the deposition process. Results from nanoindentation with dynamic mechanical analyses showed that the mechanical properties of CoCrFeMnNi HEAFs depended on the film thickness. Both the hardness and Young's modulus decreased first and then increased with the increasing film thickness. The mechanical properties were related to the microstructures of the three layers. The nonuniform structure of the 750 nm-thick film could lead to the low and uneven mechanical properties. However, the abundant nanotwins in the 1400 nm-thick film resulted in the strengthening effect. Our findings not only provide insight into understanding the thickness-dependence of the mechanical properties of CoCrFeMnNi HEAFs, but also offer clues for the MEMS to design high performance HEAFs at small-scales. Highlights: We deposited high entropy alloy films with different thicknesses and structures. Amorphous, crystalline and preferred orientation layers grew sequentially in films. Used dynamic mechanical analyses to probe thickness-dependent mechanical properties. We correlated mechanical properties with structures of the three layers in the film. Nanotwins and small grain sizes in films contributed to the strengthening effect.